Mez's magic - Schrefer, Eliot, 1978- (Schrefer, Eliot, 1978- Lost rainforest, 2018)
Caldera is divided into animals who walk by night and those who walk by day. Mez and her sister are nightwalker panthers who fear daywalkers as creatures of myth and legend. When Mez discovers that she can enter the daylight world, she and an unlikely group of animal friends including a bat, a tree frog, and a monkey, must unravel an ancient mystery, discover the extent of Mez's newly discovered magical powers, and face their greatest fears in order to save their rainforest home.